6th Nordic Workshop on Reindeer Research, 8-10 October 1990, Tromsø, Norway. - Skjenneberg (ed.), Sven (Rangifer, 1990)
TheSixth Nordic Reindeer Scientist's Meeting, organised by the Nordic Council for Reindeer Research, was held at Tromsø, Norway,8-10 October, 1990. The principal themes of the meeting were ' Reindeer husbandry. Basis for resources and the man' and ' Meat quality'.